There is always Sorrow: Risk Factors Faced by Parents of Children Presenting with Severe Intellectual Disabilities - Buthelezi, Sandisiwe; Mawila, Daphney (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: This study investigates the risk factors faced by parents of children with Severe Intellectual Disabilities. Methods: This study used a phenomenological research design within a qualitative research approach. Six parents of children diagnosed with Severe Intellectual Disability at Learners with Special Educational Needs schools were purposively selected to participate in this study. Data were collected through semi-structured interviews and a focus group. Thematic data analysis was used to analyze data. Results: The findings of this study revealed that parents of children with Severe Intellectual Disabilities faced risks that exacerbated negative outcomes. Psychological distress, social exclusion and isolation, financial burdens, and lack of access to formal education were risk factors that hindered their ability to care for and support their children. Conclusions: Based on these findings, the study concluded that parents need access to multidisciplinary teams of healthcare professionals to support them in combatting the risk factors they face.